2020
DOI: 10.21203/rs.2.23608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High dose saccharin supplementation does not induce gut microbiota dysbiosis or glucose intolerance in healthy humans and mice

Abstract: Background : Non-caloric artificial sweeteners (NCAS) are widely used as a substitute for dietary sugars to control body weight or glycemia. Paradoxically, saccharin and other NCAS have been reported to induce glucose intolerance in mice fed a high-fat diet and in a subset of humans by directly inducing unfavorable changes in gut microbiota. These findings have raised concerns about NCAS and called into question their broad use. Whether these results can be generalized to healthy populations consuming conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…Members achieved the maximum ADI of substances for two weeks. The results did not reveal any changes in taxonomic levels of microorganisms or metabolomics profiles compared to the control group [43].…”
Section: Saccharincontrasting
confidence: 54%
See 1 more Smart Citation
“…Members achieved the maximum ADI of substances for two weeks. The results did not reveal any changes in taxonomic levels of microorganisms or metabolomics profiles compared to the control group [43].…”
Section: Saccharincontrasting
confidence: 54%
“…During this experiment, the numbers of Lactobacillus located in caecal increased after intervention with saccharin. Moreover, another experiment conducted by Suez et al found out that a saccharin diet can help to reduce the lactobacilli from metabolism [43,44,45]. The study from 2021 made by Shil et al focused on the models of microbiota with Escherichia coli and Enterococcus faecalis.…”
Section: Saccharinmentioning
confidence: 99%